HUBUNGAN POWER OTOT TUNGKAI DAN DAYA TAHAN DENGAN HASIL SHOOTING PADA TIM SEPAK BOLA SSB UNRI U-15 - Roy Fadilla Silitonga; Slamet Slamet; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The purpose of this study was to determine the correlation between leg muscle power and endurance with shooting on the Tim SSB Unri U-15. This research belongs to the type of correlational research (Correlation Research). The population of this research is the 20-person Tim SSB Unri U-15. This study uses a total sampling technique (saturated sample), in which the entire population is sampled. From the results of this study it is known that there is a relationship between leg muscle power and the accuracy of shooting soccer in the Tim SSB Unri U-15, the calculated value is 0.674. From the table r values obtained rtabelpada df = 18 with a significant level (α) 0.05 = 0.444. This means that the calculated value is 0.674> rtable (0.444). The relationship of endurance to the accuracy of shooting soccer game on the Tim SSB Unri U-15 team got a calculated value of 0.468. From the table r values obtained rtabelpada df = 18 with a significant level (α) 0.05 = 0.444. This means that the calculated value is 0.468> rtable (0.444). The results of the calculation of the correlation obtained rcount value of 0.672. From the table r values obtained rtabelpada df = 18 with a significant level (α) 0.05 = 0.456. This means that the calculated value is 0.672> rtable (0.456), meaning that the hypothesis is accepted and there is an ankle relationship with booting accuracy in the game of football in the Tim SSB Unri U-15.Key Words: Explosive Power, Endurance, Shooting